2008
DOI: 10.4321/s0212-71992008000500008
|View full text |Cite
|
Sign up to set email alerts
|

Quiste de paratiroides recurrente: A propósito de un caso

Abstract: The parathyroid cyst is a very infrequent entity, so much so that only round about 200 cases have been described up to now. It can be functional and non-functional. The studies of image don't clarify to us if procedence becomes of parathyroid or it has another origin, and the diagnosis is made with the analysis come from the liquid obtained in the puncture aspiration, where high PTH's concentrations are seen. Surgery is the treatment for functional cysts and the puncture aspiration for non- functional, the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…No recurrences or metastasis is observed, except for 14 cases of patients, from whom 10 patients appeared with 1 recurrence, 3 with 2 recurrences, and 1 with 3 recurrences within their follow-up period. [ 2 , 40 , 54 , 65 , 166 , 169 , 170 , 210 , 215 , 220 , 223 , 224 ] These recurrences appeared after the first FNA and surgical excision was mandatory as their definitive treatment. According to a study published by Lorenzo et al [ 224 ] in 2008, malignant transformation has not been noted in 10 years follow-up of a case of a recurrent PC, which needed repeated FNA due to patient's rejection to be operated.…”
Section: Discussionmentioning
confidence: 99%
“…No recurrences or metastasis is observed, except for 14 cases of patients, from whom 10 patients appeared with 1 recurrence, 3 with 2 recurrences, and 1 with 3 recurrences within their follow-up period. [ 2 , 40 , 54 , 65 , 166 , 169 , 170 , 210 , 215 , 220 , 223 , 224 ] These recurrences appeared after the first FNA and surgical excision was mandatory as their definitive treatment. According to a study published by Lorenzo et al [ 224 ] in 2008, malignant transformation has not been noted in 10 years follow-up of a case of a recurrent PC, which needed repeated FNA due to patient's rejection to be operated.…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that the larger the cyst is, the more likely it is to relapse after the procedure. Sclerosing agent injections are not recommended because they can flow out from the capsule and cause serious complications such as fiber degeneration or damage to the recurrent laryngeal nerve, resulting in vocal cord paralysis [ 26 , 27 ]. It has been suggested that the optimal treatment for symptomatic NFPCs is surgical resection [ 1 , 28 ].…”
Section: Discussionmentioning
confidence: 99%